2015
DOI: 10.1002/eji.201545739
|View full text |Cite
|
Sign up to set email alerts
|

Antigen archiving by lymph node stroma: A novel function for the lymphatic endothelium

Abstract: Secondary lymphoid stroma performs far more functions than simple structural support for lymphoid tissues, providing a host of soluble and membrane-bound cues to trafficking leukocytes during inflammation and homeostasis. More recently it has become clear that stromal cells can manipulate T cell responses, either through direct antigen-mediated stimulation of T cells or more indirectly through the retention and management of antigen after viral infection or vaccination. In light of recent data, this review pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 92 publications
(156 reference statements)
0
20
0
Order By: Relevance
“…While a substantial proportion of antigen is recycling, 60% of antigen is not recycling within 3 h . FDC can hold intact antigen in the form of immune complex for many months . The presence of a second intracellular reservoir may be important, as it may represent a protected habitat where antigen is held for prolonged periods, possibly occasionally presented to reactivate B cells over sustained periods.…”
Section: B‐cell Selection In Gcmentioning
confidence: 99%
“…While a substantial proportion of antigen is recycling, 60% of antigen is not recycling within 3 h . FDC can hold intact antigen in the form of immune complex for many months . The presence of a second intracellular reservoir may be important, as it may represent a protected habitat where antigen is held for prolonged periods, possibly occasionally presented to reactivate B cells over sustained periods.…”
Section: B‐cell Selection In Gcmentioning
confidence: 99%
“…Fibroblasts and non-endothelial stromal cells comprise a large portion of the lymph node stroma and are capable of presenting peripheral tissue antigens, but their capacity to acquire and present foreign antigens is not yet well understood 28,29,30 . We were unable to detect antigen archiving by blood endothelial cells or fibroblasts in our initial studies 12,13 . While LECs have been shown to present antigens in the absence of inflammation to induce T cell tolerance 31,32,33,34,35,36,37,38 , we showed that presentation of archived antigen occurs only after exchange of the archived antigen from an LEC to a migratory DC; changing the stimulus from tolerizing to immunostimulatory 12,13 .…”
Section: Introductionmentioning
confidence: 82%
“…We were unable to detect antigen archiving by blood endothelial cells or fibroblasts in our initial studies 12,13 . While LECs have been shown to present antigens in the absence of inflammation to induce T cell tolerance 31,32,33,34,35,36,37,38 , we showed that presentation of archived antigen occurs only after exchange of the archived antigen from an LEC to a migratory DC; changing the stimulus from tolerizing to immunostimulatory 12,13 . Soluble antigens are exchanged via two distinct mechanisms: (i) direct exchange between LECs and migratory DCs and (ii) LEC death.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…These include not only the recruitment and delivery of inflammatory cells to the skin, but also the release of cytokines and chemokines. Additionally, endothelial cells are present in secondary lymphoid organs [1], including skin-draining lymph nodes, and have immunoregulatory effects at those sites [2]. Blood vessels in the skin are intimately associated with sensory and sympathetic nerves as are the secondary lymphoid organs [3-5].…”
Section: Introductionmentioning
confidence: 99%